2011
DOI: 10.1016/j.cell.2011.09.035
|View full text |Cite
|
Sign up to set email alerts
|

The Eph-Receptor A7 Is a Soluble Tumor Suppressor for Follicular Lymphoma

Abstract: Insights into cancer genetics can lead to therapeutic opportunities. By cross-referencing chromosomal changes with an unbiased genetic screen we identify the ephrin receptor A7 (EPHA7) as a tumor suppressor in follicular lymphoma (FL). EPHA7 is a target of 6q deletions and inactivated in 72 % of FLs. Knockdown of EPHA7 drives lymphoma development in a murine FL model. In analogy to its physiological function in brain development, a soluble splice variant of EPHA7 (EPHA7TR) interferes with another Eph-receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
148
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 151 publications
(154 citation statements)
references
References 60 publications
(83 reference statements)
4
148
0
2
Order By: Relevance
“…S10G). To ensure this effect was not the result of cosegregation between CREBBP mutations and deletions of the MHC class II locus, we interrogated somatic copy number data from our exome series and additional publicly available high-resolution data (12,13,(22)(23)(24). Although we detected deletions of the MHC class II locus in a subset of patients (SI Appendix, Fig.…”
Section: Frequent Cooccurring Mutations Of Chromatin-modifying Genes mentioning
confidence: 99%
“…S10G). To ensure this effect was not the result of cosegregation between CREBBP mutations and deletions of the MHC class II locus, we interrogated somatic copy number data from our exome series and additional publicly available high-resolution data (12,13,(22)(23)(24). Although we detected deletions of the MHC class II locus in a subset of patients (SI Appendix, Fig.…”
Section: Frequent Cooccurring Mutations Of Chromatin-modifying Genes mentioning
confidence: 99%
“…More recently, Oricchio et al performed a systematic screen of genes within commonly deleted regions on the long arm of chromosome 6 (45), motivated by the high frequency of 6q deletions in FL as well as their association with adverse outcome (41). This screen revealed TNFAIP3/A20, a negative regulator of NF-κB signaling, as well as the receptor tyrosine kinase EPHA7 as potential tumor suppressors in FL (45). The authors demonstrated that silencing of EPHA7 decreased lymphomagenesis latency in VavP-BCL2 transgenic mice, and that restoration of its tumor suppressor function through administration of exogenous EPHA7 delayed tumor formation in xenograft models.…”
Section: Genetic Landscape Of Flmentioning
confidence: 99%
“…To ensure potent knock down as single-copy integrants, the shRNAs were cloned in the context of an miR-30 backbone in an MSCV-based, GFP-expressing vector (32). Based on initial "reconstruction" studies, the Cancer 1,000 library was subdivided in six pools, each containing 288 shRNAs, and supplemented with a seventh pool comprising 260 additional shRNAs against cancer-related genes (1-7 shRNAs per gene) (33). After transduction with the seven pools of shRNAs from the modified Cancer 1,000 library, the 4TO7-TGL cells were injected into the tail vein of 49 recipient mice (Fig.…”
Section: Gain-of-function Screens Identify Micrornas That Promote Metmentioning
confidence: 99%